Utilizing the internet of things (IoT) to develop a remotely monitored autonomous floodgate for water management and control - Hajjaj S.S.H.; Sultan M.T.H.; Moktar M.H.; Lee S.H. (MDPI AG, 2023)
Flood control; Floods; Gateways (computer networks); Hydraulic gates; Open systems; Water management; Flood management; Floodgates; Internet of Things (IOT); Open source development; Open sources; Pi systems; WATERGATE; Internet of things; autonomy; control system; coordinate; flood control; Internet; water management; Rubus glaucus